Determination of Second Order Polynomial Curve Fitting for Length- Weight Relationship of Cirrhina mrigala from Munj Sagar Talab Dhar, Madhya Pradesh, India - Amita Dagaonkar; Man Mohan Prakash; Nagesh Dagaonkar (New Visions in Biological Science Vol. 7, 2021)
From November 2006 to October 2008, the Cirrhina mrigala of the Munj Sagar talab Dhar was investigated for its weight-length relationship. Cirrhina mrigala has a useful length–weight relationship (LWR) of 2.869. In predicting and planning the ecosystem, statistical tools such as co- relation, smoothing of data, regression and cluster analysis, and polynomial curve fitting are useful. In the present study several order of polynomial fitting was tried among the different parameters using the Origin 6.0 software. The Second order polynomial was found to be a best fit for LWR..